2017
DOI: 10.1177/0193945917715261j
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychological Effects of Qigong Exercise in Community-Dwelling Older Adults: An Exploratory Study

Abstract: This study aimed to translate and evaluate the psychometric properties of a Chinese version of the Dutch Eating Behavior Questionnaire for Children (DEBQ-C) among Taiwanese preadolescents. Consisting of three subscales (emotional, restrained, and external eating), the DEBQ-C is used to measure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 7 publications
2
16
1
Order By: Relevance
“…The preliminary efficacy of Health Qigong on physical and psychological health and spiritual well-being will be published elsewhere (in review). 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary efficacy of Health Qigong on physical and psychological health and spiritual well-being will be published elsewhere (in review). 14…”
Section: Resultsmentioning
confidence: 99%
“…28 Moreover, as previous research revealed the potential implication of spirituality in meditative movement including Qigong, 29,30 the results of our study also suggests that spirituality may be another crucial factor that can potentially influence Qigong exercise adherence and acceptance in older adults, as well as have a positive impact on physical and psychological well-being. 14…”
Section: Various Forms Of Qigong Exercises Have Been Investigated In mentioning
confidence: 99%
“…Specifically targeted for the practice of Qigong might be arthritis patients with comorbid diseases such as heart disease and/or diabetes, those who are overweight, those who have intractable pain [ 72 ], those with sleep challenges, those who cannot take medication, those at risk for falling, those at risk of poor adherence to regular exercise, and those who are depressed or anxious. These arthritis sub-groups groups may all be especially benefited [ 33 , 56 , 57 , 66 , 70 , 73 , 74 ], even if the exercises are only carried out for short periods, and the benefits are only perceived as benefits by the participants [ 75 ], such as increased ‘vitality’ [ 74 ] and ‘life quality’ [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prática do Chi Kung/Qi Gong e seus benefícios. Os artigos publicados (CHAN et al 2016;CHANG et al 2018a;CHANG et al 2018b;GUO et al 2018a;GUO et al 2018b;JING et al 2018;KELLEY & KELLEY, 2015LADAWAN et al 2017LIU et al 2015;MARTÍNEZ, N. 2015;PORTER 2015;TAVARES et al 2016;TSANG et al 2015;WALTHER et al 2018;ZOU et al 2018a;ZOU et al 2018b) (ZOU et al 2018).…”
Section: As Práticas Integrativas E Complementares E a Psicologiamentioning
confidence: 99%